2022
DOI: 10.1186/s13046-022-02455-6
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke phytocomplex modulates serum microRNAs in patients exposed to asbestos: a first step of a phase II clinical trial

Abstract: Background Malignant pleural mesothelioma is a highly aggressive tumor associated with asbestos exposure. There are few effective treatment options for mesothelioma, and patients have a very poor prognosis. Mesothelioma has the potential to represent an appropriate disease to prevent because of its strong association with asbestos exposure and the long latency from exposure to the disease on-set. Methods In the present study, we tested biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A previous study showed the protective effect of an artichoke extract on pleural mesothelioma in a sample of 18 individuals with asbestos-related benign pleural disease (Muti et al, 2022). A study by Pulito et al (2015) found the antitumor effect of ALE against malignant pleural mesothelioma in vivo and in vitro.…”
Section: Anticancer Activitymentioning
confidence: 95%
“…A previous study showed the protective effect of an artichoke extract on pleural mesothelioma in a sample of 18 individuals with asbestos-related benign pleural disease (Muti et al, 2022). A study by Pulito et al (2015) found the antitumor effect of ALE against malignant pleural mesothelioma in vivo and in vitro.…”
Section: Anticancer Activitymentioning
confidence: 95%
“…The anticancer activity of artichoke is well reported in the scientific literature. A previous study showed the protective effect of an artichoke extract on pleural mesothelioma in a sample of 18 individuals with asbestos-related benign pleural disease (Muti et al, 2022). ALE exerts antitumor effect against malignant pleural mesothelioma in vivo and in vitro (Pulito et al, 2015).…”
Section: Anticancer Activitymentioning
confidence: 99%